Does job loss make you smoke and gain weight? - Jan Marcus (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper estimates the effect of involuntary job loss on smoking behavior and body weight using German Socio-Economic Panel Study data. Baseline nonsmokers are more likely to start smoking due to job loss, while smokers do not intensify their smoking. Job loss increases body weight slightly, but significantly. In particular, single individuals as well as those with lower health or socioeconomic status prior to job loss exhibit high rates of smoking initiation. The applied regression-adjusted semiparametric difference-in-difference matching strategy is robust against selection on observables and time-invariant unobservables. This paper provides an indirect test showing that the identifying assumption is not violated in the difference-in-difference estimator. The findings are robust over various matching specifications and different choices of the conditioning variables.
Keywords: I12; J65; 330; job loss; smoking; body weight; health behavior; difference-in-difference; propensity score matching; Arbeitslosigkeit; Rauchen; Körpergewicht; Schätzung; Deutschland